Prosedur Penggunaan Alat Fiksasi Masker Termoplastik Pada Terapi Radiasi Kasus Kanker Payudara Di Instalasi Radioterapi RSUP Dr. Hasan Sadikin Bandung - Sanita Sihotang; Anak Agung Aris Diartama; Retno Laksmi Faraningrum (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Breast cancer is a type of cancer that often occurs in women, in the treatment of breast cancer is radiotherapy and fixation tools used, namely breast boards and thermoplastic masks which are aids for patients not to move during radiation therapy. The purpose of the study was to determine the procedure and reasons for using thermoplastic mask fixation devices in radiation therapy cases of breast cancer. This research is qualitative with a case study approach, the research time is from June 7 to July 15, 2023 and the research location at the Radiotherapy Installation of Dr. Hasan Sadikin Hospital Bandung. The subjects of the study were Radiation Oncology Doctors, Medical Physicists, Radiotherapists and Patients. By collecting data, making interview transcripts and reducing data and processed with open coding, given in the form of quotations and then drawing conclusions.The results showed that the procedure for using a thermoplastic mask fixation device was inserted into a waterbath with a temperature of 65.50C until the thermoplastic mask became flexible, the reason for using fixation was a shift in smaller objects at the time of irradiation, and better aesthetic value, because concentration marks and field boundaries did not need to be drawn directly on the patient's body but were drawn on the thermoplastic mask. Using a mask does not need to be marked on the patient's chest so that by using a thermoplastic mask the shift towards the target object is smaller during irradiation.